2003
DOI: 10.1002/dc.10261
|View full text |Cite
|
Sign up to set email alerts
|

Mollaret's meningitis: Cytopathologic analysis of fourteen cases

Abstract: Mollaret's meningitis (MM) is a rare disease of benign nature characterized by recurrent episodes of aseptic meningitis. Cerebrospinal fluid (CSF) examination remains the sole diagnostic modality. Eighteen CSF samples from 14 patients were studied along with the clinical data. Specimens were prepared by cytocentrifugation and Millipore filtration and were stained with Diff-Quik and Papanicolaou stains. Eight patients were men and six were women, with an age range of 17-74 yr (mean age 37 yr). Most common clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Symptomatic episodes of RLM usually subside within 5 years, but the total number of episodes may reach 30. Patients are typically middle-aged, and women are more often affected than men ( 1 3 ). In addition to symptoms typical of meningitis, ≈50% of patients have transient hallucinations, seizures, cranial nerve palsies, or an altered level of consciousness ( 4 ).…”
mentioning
confidence: 99%
“…Symptomatic episodes of RLM usually subside within 5 years, but the total number of episodes may reach 30. Patients are typically middle-aged, and women are more often affected than men ( 1 3 ). In addition to symptoms typical of meningitis, ≈50% of patients have transient hallucinations, seizures, cranial nerve palsies, or an altered level of consciousness ( 4 ).…”
mentioning
confidence: 99%
“…Since then, electron microscopy and immunohistochemistry have confirmed this cell to be a monocyte [2]. Although our patient had a 4-day history of disease, Mollaret cells are usually present during the acute phase of the disease and are most prevalent during the first 24 h, and therefore they can be easily missed [2].…”
mentioning
confidence: 85%
“…It was thought that over time, the number of recurrent episodes of MM decrease, but several cases of this entity reported in older patients (Monteyene et al, 1996;Ruben, 1994;Szabo et al, 1983;Chan et al, 2003;Tedder et al, 1999;Pisani, Fattorello, Leotta, Marcello, & Zuliani, 1999;Ikari, Kuzuya, Yoshimine, Sugita, & Kazuya, 1993) suggest that advancing age is not protective (Monteyene et al, 1996;Tedder et al, 1994;Dylewski & Bekhor, 2004). This phenomenon also may be explained by eventual reactivation of the CNS T. gondii infection/inflammation in these elderly subjects with MM, because general population studies performed in adult subjects showed that plasma levels of TNF-α, sTNF-R p55 and p75, and IL-6 are significantly increasing with age (Himmerich et al, 2006).…”
Section: Female Predominancementioning
confidence: 96%
“…The cerebrospinal fluid (CSF) contains large friable mononuclear cells thought to be of endothelial origin (vasculitis?) (Szabo, Majtenyi, & Guseo, 1983;Bamborschke, Sandmann, & Wullen, 1990;Pampliega-Perez et al, 2003), with blunt pseudopods (a "footprint" appearance) and bean-shaped and bilobed nuclei (Evans, 1993;Chan, Parvani, Levi, & Ali, 2003;Sendi & Garber, 2006). These cells, observed for only the first 24 hr ("ghosts" cells) and now considered to be activated macrophages (Ginsberg, 2004), may comprise 60%-70% of cells in the CSF.…”
Section: Introductionmentioning
confidence: 95%